Analisis Pengaruh Variasi Kecepatan LRT Jabodebek Pada Longspan Terhadap Ride Index Menggunakan Simulasi Longitudinal Train Dynamic (Politeknik Perkeretaapian Indonesia Madiun, 2022)
Speed is one of the factors supporting passenger comfort in rail transportation. The problem that occurs when the train is on a longspan is that the speed does not affect passenger comfort. The solution to this problem is that the train must go through a simulation process with the aim of knowing the efficient speed received by prioritizing comfort when passing a longspan. The simulation was carried out using the Longitudinal Train Dynamic (LTD) method by comparing the ride index value of the simulation results with the ride index value set in KP 765 of 2017 concerning the Design and Specifications of the Jabodebek LRT which refers to ISO 2631 Jabodebek. Based on the standards determined, the researchers carried out simulations with variations in speed to determine the effect of speed variations on the travel index value, so that the efficient speed at the longest long span of passengers was known. The simulated speeds are 10 kmh, 20 kmh, 30 kmh, 40 kmh, 50 kmh, and 60 kmh. The data from this study is the ride index value of the simulated speed variation. The results of this study are the ride index value at a speed of 10 kmh is 1.4747427, 20 kmh is 1.6533716, 30 kmh is 1.8409451, 40 kmh is 2.2335365, 50 kmh is 2.4009598, and 60 kmh is 2.6713053. And the optimal speed of the Jabodebek LRT is in the range of 30-40 kmh.